The Relationship Between Work Duration and Carpal Tunnel Syndrome in Cigarette Rolling Workers - Firdaus, Fisabili; Prihatin, Murwani Yekti; Romadhoni, Romadhoni; Setiawan, Muhammad Riza (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: This study aimed to identify the correlation between the length and the period of Work correlated with the incidence of carpal tunnel syndrome among cigarette rolling workers at the Breadfruit Factory. Methods: This is an analytic observational study with a cross-sectional method. It utilizes the sample selection method of purposive sampling. The information collection tool consists of questions covering personal information, length of service, and physical examination sheets. Statistical test implemented with Chi-square. Results: The number of cigarette rolling workers used as the sample for this study was 103 people. The statistical test results applying chi-square work duration obtained p-value = 0.005 (p ≤0.05), a p-value of 0.000 (p ≤0.05) was obtained for years of service, indicating a correlation between length of Work and working time with the possible occurrence of Carpal Tunnel Syndrome (CTS) in workers. Conclusion: There is a significant correlation between length of Work and duration of Work on the emergence of CTS symptoms. As a form of prevention, occupational health and safety nurses can provide adequate education to cigarette companies to pay attention to employee conditions and the possibility of health problems occurring for their employees.